The Potential Use of Mesenchymal Stem Cells and Their Derived Exosomes as Immunomodulatory Agents for COVID-19 Patients - Faisal A. Alzahrani; Islam M. Saadeldin; Abrar Ahmad; Dipak Kumar; Esam I. Azhar; Arif Jamal Siddiqui; Bassem Kurdi; Abdulrahim Sajini; Abdulmajeed F. Alrefaei; Sadaf Jahan (Stem Cells International)
A novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) causing lethal acute respiratory disease emerged in December 2019. The World Health Organization named this disease “COVID-19” and declared it a pandemic on March 11, 2020. Many studies have shown that mesenchymal stem cells (MSCs) and their exosomes (MSCs-Exo), which are isolated from allogenic bone marrow stem cells, significantly lower the risk of alveolar inflammation and other pathological conditions associated with distinct lung injuries. For example, in acute respiratory distress syndrome (ARDS) and pneumonia patients, MSCs-Exo and MSCs provide similar healing properties and some clinical trials have used cell-based inhalation therapy which show great promise. MSCs and MSCs-Exo have shown potential in clinical trials as a therapeutic tool for severely affected COVID-19 patients when compared to other cell-based therapies, which may face challenges like the cells’ sticking to the respiratory tract epithelia during administration. However, the use of MSCs or MSCs-Exo for treating COVID-19 should strictly adhere to the appropriate manufacturing practices, quality control measurements, preclinical safety and efficacy data, and the proper ethical regulations. This review highlights the available clinical trials that support the therapeutic potential of MSCs or MSCs-Exo in severely affected COVID-19 patients.